Status of Sustainability Mangrove Ecosystem in Ecomarine Mangrove Muara Angke, Jakarta - Talida Salma Khairunnisa; Sri Mulatsih; Efi Yuliati Yovi (Postgraduate, University of Mataram, 2025)
The northern coast of Jakarta has experienced mangrove forest degradation and loss of natural protection from abrasion, tidal flooding, and storms. However, awareness of the need for mangrove rehabilitation has grown in recent decades, with one location being the Kali Adem delta by community named Komunitas Mangrove Muara Angke (KOMMA). These mangroves must be managed sustainably to ensure that their benefits can be felt over the long term. This study aims to analyze the sustainability of mangrove ecosystem management in the Muara Angke Ecomarine Mangrove. A multidimensional scaling (MDS) approach using the Rapid Appraisal for Fisheries (RAPFISH) ordination technique was employed. The results indicate that the sustainability status of mangrove ecosystem management at Ecomarine Mangrove Muara Angke falls into the moderately sustainable category with an index value of 53.14. However, one of the four dimensions with a low value is the economic dimension. The sustainability index value for the economic dimension is 44.73, with the key factor that need to be considered is the additional income of the Muara Angke community. Efforts to manage mangroves must be enhanced to ensure the continued existence of mangroves in Muara Angke and to provide benefits for the environment and socio-economic well-being.